Fermentation of cocoa (Theobroma cacao L.) beans using Candida sp. and Blastobotrys sp - Mahazar, Nurul Husna (2015)
Spontaneous fermentation often produces a variety of end products. Starter culture has been widely used in many fermented food in order to control fermentation process and produce consistent products. The objective of this study was to evaluate the effect of Candida sp. and Blastobotrys sp. as starters in cocoa bean fermentation in term of optimal media culture, survivability of the cultures and fermentation products of cocoa bean fermentation (pH, temperature, microbial count, proximate analyses, bioactive compounds and volatile compounds). Optimum formulation of molasses yeast extract (MYE) media for the growth of Candida sp. and Blastobotrys sp. was determined using response surface methodology (RSM). Survivability of the cultures was measured by counting of colony-forming units (cfu) on yeast peptone dextrose (YPD) media. Sugar utilization by both types of yeasts in the optimum MYE media were determined using high performance liquid chromatography (HPLC) analysis. The yeasts were then used as a starter culture in cocoa bean fermentation and the products were evaluated for pH, temperature, proximate content, microbial safety and volatile compounds. The results showed that optimal concentrations of MYE medium were determined as follows: Candida sp. (2 g/100 ml, yeast extract; and 10 g/100 ml, molasses) and Blastobotrys sp. (2 g/100 ml, yeast extract; and 1.92 g/100 ml, molasses). The optimum MYE media was able to support the growth of Candida sp. and Blastobotrys sp. up to 140 and 70 days at room temperature, respectively. During survivability of yeasts, both of yeasts rapidly consumed glucose and fructose compared to sucrose at the beginning of the fermentation. Cocoa beans in spontaneous fermentation, Blastobotrys sp.-fermentation and Candida sp.-fermentation raised in temperature from 32°C (day 0) to maximum temperature valued 40°C, 42°C and 43°C after 3 days fermentation, respectively. The pH of cocoa for spontaneous fermentation, Blastobotrys sp.-fermentation and Candidasp.-fermentation at beginning of process were pH 4.07, 4.11 and 4.19, respectively, then the pHs of end products were 5.15, 5.44 and 4.99, respectively. Microbial safety of all type of fermentation showed that the number of E. coli and Salmonella sp. were decreased from 103 - 105 cfu/ml to significant (p<0.05) decreases of crude protein (13.86 - 9.83%), (14.50 - 11.99%) and (14.89 - 13.04%) after 7 days fermentation. Significant decrease in carbohydrate content (32.01% - 12.98%) was observed in spontaneous fermentation only. However, Blastobotrys sp.-fermentation and Candida sp.-fermentation showed increase of carbohydrate value from 9.84 to 19.98% and 22.53 to 22.64%. Spontaneous fermentation showed significant increase in fat (41.51 - 60.32%) and crude fibre content (3.83 - 8.79%) of fermented beans. Significant decreased in ash content for spontaneous fermentation and Blastobotrys sp.-fermentation were (4.44 - 3.06%) and (3.88 - 3.15%), respectively. Significant decreased in moisture content was observed in and Blastobotrys sp.-fermentation (6.84 - 4.71%) and Candida sp.-fermentation (8.20 - 5.69%) but significant increase was observed from spontaneous fermentation (4.34 - 5.02%). Blastobotrys sp.-fermentation product contained low in caffeine (30.59%) while Candida sp.-fermentation product contained low in theobromine (16.53%) but high in stigmasterol (1.68%), beta-sitosterol (3.03%) and tocopherol (5.38%). Fermentation showed a total of 20 volatile compounds related to the desirable notes and off-flavour. High individual compounds of alcohol (5) and ester (6) were detected from Blastobotrys sp.-fermentation compared to spontaneous fermentation; alcohol (3) and ester (4), and Candida sp.-fermentation: alcohol (4) and ester (2). Based on these findings, Candida sp. and Blastobotrys sp. could be used as potential starter cultures for cocoa beans fermentation.